The Impacts of Feeding a Reduced Energy and Lysine Balance in Lactation on Sow Body Composition, Litter Growth, and Markers of Subsequent Reproductive Performance - Tracy L. Muller; Kate J. Plush; John R. Pluske; Darryl N. D’Souza; David W. Miller; Robert J. Van Barneveld (Agriculture)
This experiment examined whether multiparous sows fed a diet lower in energy and lysine at a reduced feed allowance would still mobilise fat and (or) protein to support piglet growth and negatively impact subsequent reproductive performance. A total of 152 multiparous sows was allocated in a 2 × 2 factorial design with the respective factors being diet type fed in lactation (gestation, 13.0 MJ digestible energy (DE)/kg, 0.42 g standardised ileal digestible (SID) lysine/MJ DE; or lactation, 14.3 MJ DE/kg, 0.62 g SID lysine/MJ DE) and feed allowance (ad libitum or 7.5 kg/d, ~15% reduction on ad libitum intake). Body composition was estimated on the day after farrowing (day 2) and at weaning (day 21). Blood was collected on days 2, 21 and at standing heat, for the analysis of insulin and insulin-like growth factor 1 (IGF-1). Diet type did not alter (p > 0.05) bodyweight or P2 backfat depth change in lactation, estimated body fat and protein changes, litter growth, or subsequent total piglets born. Ad libitum-fed sows showed a significant gain in girth compared to sows offered 7.5 kg/d (2.9 versus −0.4 mm, p = 0.015) and had a tendency for a shorter wean-to-service interval (p < 0.10). Sows fed the lactation diet had higher insulin concentrations at weaning (p < 0.05), but levels were the same (p > 0.10) by heat detection; IGF-1 concentrations remained unaffected. These data indicate that imposing a calculated negative energy and lysine balance on lactating sows had a limited impact on lactation or subsequent reproductive performance, supporting the notion that the modern sow may be more resilient to nutritional impositions than has been historically reported.